KESINAMBUNGAN SENI RUPA INDONESIA (DITINJAU DARI BAHASA RUPA TRADISI) - Sri Marwati (Pendhapa, 2012)
Indonesia is a rich country with tradition cultural which heritaged from ancestral. As relics of the reliefs in some temples in Indonesia. We have the different character from other nations and the most important is the Indonesia human has features works of art that has existed since prehistoric times and the characteristic can still be found in the present. There is a continuity of the Indonesian art with the art of first ancestor. The characteristics include the Flat Time Space system (in Indonesian called Ruang Waktu Datar) that is different directions, different place, and different time. Many artists of Indonesia implementing this RWD system is realized or not, this is definitely RWD system is a system that has been done by the ancestors of Indonesia.Â Keyword: continity, fine art, tradition